Knowledge and beliefs on corneal donation in Singapore adults. Issue 7 (17th June 2005) - Yew, Y-W; Saw, S-M; Pan, J C-H; Shen, H-M; Lwin, M; Yew, M-S; Heng, W-J
Abstract : Aim: To assess the knowledge and willingness of Singapore adults towards corneal donation. Methods: The study population consists of a cluster random sample of the population living in Bedok North (an area in the eastern part of Singapore). The study population comprised residents aged 21–65 years living in 675 randomly sampled housing units. The participation rate was 65.9% (544/825). All participants were interviewed face to face with a questionnaire formulated according to the modified Horton and Horton model. Knowledge, values, attitudes, and spiritual beliefs of participants were assessed to evaluate their willingness to donate their corneas. Results: 67.0% of participants were willing to donate their corneas. Ethnicity (Chinese) and religion (Christians, Hindus, or those with no religion) were associated with increased willingness to donate corneas. Greater knowledge and increased altruistic values were also associated with increased willingness to donate corneas. Conclusion: A proportion of participants were willing to donate their corneas. Awareness of corneal donation is high but specific knowledge should be further increased among adults.